Analysis of Urban Stormwater Management Based on the "Sponge City" Strategy-Stormwater Landscape Park - Xu, Deming; Jiang, Daowei (International Journal of Natural Resources and Environmental Studies, 2024)
Due to the increasing trend of urbanization and climate change in China, the domestic rainfall has reached a level that is difficult to digest. From the current situation of major cities in China, most cities are threatened by surface water flooding. Landscape design can play a crucial role in solving this problem - rainwater landscape parks can be integrated with ecological facilities of different scales, and then used as green sponges to purify and store the flooded surface water in the city, and applied to protect the local environment, fill groundwater, residents' leisure and aesthetic experience.